Prevalence of Cutaneous mycosis in Baqubah City for the period from December 2021 to April 2022 - Hussein Sami Ismael; Anaam Fuad Hussain; Hayder Jasim Mohammed (Academic Science Journal)
The current study aimed for isolation and identification of fungi from:tinea types in patients who lived in Baqubah City- Diyala province, detect which clinical type of disease is the prevalent among the patients with their etiologic agents and detect the effective antifungals against isolated fungi. Eighty samples of onychomycosis swabs, nail clippings, skin fragments and hair were collected from sixty-five patients (some patients took more than one sample from them) from December 2021 to April 2022. Through direct microscopy and after culturing in the culture media, results showed that the total positive fungal isolates were 65 (81.25%) including dermatophytes 49 (75.38%) and opportunistic yeast fungi 16 (24.61%). Tinea corporis was the most common: type of dermatophytosis in that the prevalence of dermatophytosis in males was higher than in females. The effect of terbinafine, itraconazole, fluconazole and nystatin were applied on fungal growth by well diffusion method and results concluded that terbinafine was more powerful and active against dermatophytes.